Os movimentos sociocomunicativos de ativistas engajadas na luta contra o câncer de mama no Brasil - Soares, Thais Costa Cardoso (Universidade do Vale do Rio dos Sinos, 2016)
The research argues about the possibilities of bond establishment between individuals and possibilities of exercising, offered by the new technologies of communications. To accomplish it, this research analyzes the digital media developed by The Brazilian Federation of Philanthropic Breast Health Institutions (FEMAMA) and the interactions of the activists engaged on the fight against breast cancer, in these spaces. Trough theoretical research problematize the citizenship, as a guiding concept, which conducts the research practices and goes through communicational processes. It also reflects about the belonging, as a central category to the effective citizenship exercise. The research also address the techno communicative logics in which the organization’s digital spaces are involved. The investigation path concerns an epistemological reflection about methods, followed by the research procedures of documental, bibliographical, theoretical and methodological research. Besides that, the methodological strategy works through a combination of ethnographic and netnografic approaches, starting with the systemic analyses of Femama’s digital spaces, following to present activities observations and interviews with the organization’s activists. The results show the uses and appropriations the individuals do of technology during their interactions, and verifies that those communicational spaces have the potential to the exercise of communicative citizenship and to the formation of identity bonds. Although, it was possible to see that it is not enough to make the technological means to participations and interactions available to guarantee the full citizenship exercise. It is necessary to have diversity of opinions on the information’s planning and producing processes, on the discourse building methods, and on the way of thinking communications as a whole. Besides that, it became clear that the citizen perspective needs to be a part of the own organization constitution, in a structural way, which also reflect itself on daily practices.
Keywords: Cidadania comunicativa; Vínculos identitários; Movimentos sociocomunicativos; Câncer de mama; Meios de comunicação digitais; Communicative citizenship; Identity bonds; Social and communicative movements; Breast cancer; Digital media; ACCNPQ::Ciências Sociais Aplicadas::Comunicação